Effects of bottom-up factors (N-source and light) on growth and toxin content of the harmful dinoflagellate Alexandrium pseudogonyaulax - Kristof Möller; Silke Thoms; Urban Tillmann; Bernd Krock; Florian Koch; Ilka Peeken; Cédric Léo Meunier (PANGAEA, 2024)
The effect of different nitrogen sources (Experiment 1: N-deplete, NO3-, NH4+, Urea) and different light intensities (Experiment 2: 20, 100 and 200 μmol photons m-2 s-1) on the growth response and toxin content of Alexandrium pseudogonyaulax, isolated in 2020 from the Danish Limfjord, were investigated by means of bottle incubation experiments. In the 2nd experiment, the pigment content and photophysiological response of A. pseudogonyaulax was additionally assessed. The 1st experiment was started on the 18th October 2021 and finished on the 13th December 2021, while the 2nd experiment was started on the 16th March 2022 and finished on the 14th April 2022. This dataset contains all data collected within the two experiments, including cell counts, cell sizes, goniodomin A toxin contents, particular organic carbon and nitrogen, pigment contents (only exp. 2) and photophysiological parameters (only exp. 2).